Pannexin 1 channels: new actors in the regulation of catecholamine release from adrenal chromaffin cells - Momboisse, Fanny; Olivares, María José; Báez-Matus, Ximena; Guerra, María José; Flores-Muñoz, Carolina; Sáez, Juan C.; Martínez, Agustín D.; Cárdenas, Ana M. (Frontiers in Cellular Neuroscience, 2014)
Chromaffin cells of the adrenal gland medulla synthesize and store hormones and peptides, which are released into the blood circulation in response to stress. Among them, adrenaline is critical for the fight-or-flight response. This neurosecretory process is highly regulated and depends on cytosolic [Ca2+]. By forming channels at the plasma membrane, pannexin-1 (Panx1) is a protein involved in many physiological and pathological processes amplifying ATP release and/or Ca2+ signals. Here, we show that Panx1 is expressed in the adrenal gland where it plays a role by regulating the release of catecholamines. In fact, inhibitors of Panx1 channels, such as carbenoxolone (Cbx) and probenecid, reduced the secretory activity induced with the nicotinic agonist 1,1-dimethyl-4-phenyl-piperazinium (DMPP, 50 µM) in whole adrenal glands. A similar inhibitory effect was observed in single chromaffin cells using Cbx or 10Panx1 peptide, another Panx1 channel inhibitors. Given that the secretory response depends on cytosolic [Ca2+] and Panx1 channels are permeable to Ca2+, we studied the possible implication of Panx1 channels in the Ca2+ signaling occurring during the secretory process. In support of this possibility, Panx1 channel inhibitors significantly reduced the Ca2+ signals evoked by DMPP in single chromaffin cells. However, the Ca2+ signals induced by caffeine in the absence of extracellular Ca2+ was not affected by Panx1 channel inhibitors, suggesting that this mechanism does not involve Ca2+ release from the endoplasmic reticulum. Conversely, Panx1 inhibitors significantly blocked the DMPP-induce dye uptake, supporting the idea that Panx1 forms functional channels at the plasma membrane. These findings indicate that Panx1 channels participate in the control the Ca2+ signal that triggers the secretory response of adrenal chromaffin cells. This mechanism could have physiological implications during the response to stress.